(untitled) (Swiss Medical Weekly, 2019)
OBJECTIVE To evaluate the current prevalence of self-reported interpersonal violence amongst patients consulting at the emergency department (ED) of a university hospital and to describe the characteristics of the violence sustained. METHODS Ours was a cross-sectional study using a modified version of the Partner Violence Screen questionnaire, which was distributed to every patient over 16 years old consulting at the ED between the 1st and 30th September 2016. Excluded were those incapable of decision-making, unable to understand owing to language difficulties, or in police detention. Questions pertained to violence endured during the year prior to their attendance at the ED and, where relevant, the date, place, and type of violence (physical or psychological), the perpetrator and the means used (firearms or other weapons). Demographic details were taken from the hospital records. RESULTS Of 628 patients included (participation rate 86%), 19% were victims of violence, for 27% of whom it was the motive for ED attendance. The median age of these victims of violence was 28 years (interquartile range 22–43), 39% were female, 71% single and 38% foreign nationals. Typical characteristics of self-reported violence were: (1) violence sustained within the previous 24 h (26%); (2) perpetrators unknown (35%); (3) occurrence at a café, bar, restaurant or nightclub (32%); (4) use of knives (19%); (5) prior consumption of alcohol by the victims themselves (28%). Females were more susceptible to domestic violence than males (45 vs 7%), the latter mostly reporting public violence (64 vs 43% in women). CONCLUSION The prevalence of self-reported interpersonal violence has reached one patient in five in our ED. Our results underline the importance of screening for this, as well as providing the means to offer specific follow-up.